Kali Linux, an ethical hacker's cookbook : practical recipes that combine strategies, attacks, and tools for advanced penetration testing /: practical recipes that combine strategies, attacks, and tools for advanced penetration testing. (2019) - Sharma, Himanshu
No abstract available